Neoliberalism, universities, and anthropology around the world: Introduction - Domínguez, Virginia (2024)
The idea for this dossier began with a conversation over one of those long breakfasts given at conferences. It was 2014 and the blows of the 2008 economic crisis were still being felt strongly. There was growing concern in the academic field over the advancement of neoliberalism and its effects, especially given its part in the 2008 crisis and the ensuing proliferation of “austerity politics,” which included a range of policies that were implemented as intended solutions to the economic downturn in many parts of the planet (Knight and Stewart 2016; Narotzky and Besnier 2014; Narotzky and Goddard 2016; Powers and Rakopoulos 2019). Austerity policies generated new ways of understanding the future (Bryant and Knight 2019; Narotzky and Besnier 2014), new forms of employment, and new ways of living (Fernández Álvarez and Perelman 2020; Narotzky 2018)...